Learn and play out : how to develop your primary school's outside space ; learning through landscapes - Learning through Landscapes (London ; : Routledge, 2014)
Do your children know how to grow potatoes, where to see a dragon-fly or how to fire a rocket? Are you one of the 82% of teachers who thinks their school isn't making as much use of their grounds as they should? Do you know how to make the most of your outdoor teaching and learning spaces? Learn and Play Out is an inspirational, accessible and pragmatic set of resources for making changes to Primary school playgrounds in order to provide high quality learning and play experiences. Drawing on Learning through Landscapes' experience in working with thousands of primary schools, it provides practical support to improve the use, design and management of your outdoor area. More schools are seeing the benefits of their pupils spending longer periods of their school day outside, with research showing that this improves attainment, behaviour, motivation and self-esteem. For many schools however, the environment of their grounds does not meet the needs of their pupils. This toolkit helps them assess what they already have, work through what their needs are, and inspires them to take the next steps forward to make physical and practical improvements to their grounds.
Includes bibliographical references.
Keywords: Buitenleren; Playgrounds; School grounds; Schoolinrichting